1997
DOI: 10.1111/j.1574-6976.1997.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms from deep, high temperature sandstones: constraints on microbial colonization

Abstract: Cores were collected from Late Cretaceous and Early Tertiary rocks in the Piceance Basin of western Colorado, USA, to investigate the origins of subsurface microorganisms under geological conditions likely to constrain microbial transport and survival. The sampled strata from 856–862, 1996–1997 and 2091–2096 m recorded peak paleotemperatures of 120–145°C from 40–5 million years ago, while present temperatures range from 43 to 85°C. Cores were analyzed for culturable anaerobic bacteria (Fe(III)‐ and Mn(IV)‐redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…(34). Culture media were added to serum bottles and degassed with a stream of 100% CO 2 or 100% N 2 gas for 30 min prior to pressurization.…”
Section: Methodsmentioning
confidence: 99%
“…(34). Culture media were added to serum bottles and degassed with a stream of 100% CO 2 or 100% N 2 gas for 30 min prior to pressurization.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies of the microbial diversity of deep aquifers have been published, but deep water-bearing formations are potential ecological niches for Desulfotomaculum and Desulfosporosinus species (Colwell et al, 1997; Detmers et al, 2001, 2004; Stahl et al, 2002). Studies of a pristine aquifer have shown a presence of Desulfotomaculum spp.…”
Section: Distribution Of Desulfotomaculum Spp In Different Subsurfacmentioning
confidence: 99%
“…Geological tests have shown that microorganisms traveled through the less porous sandstones (8.5–20%) at Cerro Negro, New Mexico, USA over a distance of 100 m, at depth of ~300 m, in less than 3.4 million years via a ground water velocity of 0.1 m yr −1 (Walvoord et al, 1999). The microbial colonization of a low permeability sterilized sandstone (porosity of 1–12%) in the Piceance Basin, western Colorado, USA down to the depth of 860 m had occurred in less than 5 million years (Colwell et al, 1999). The microbial transport in fractured basement rocks is even less certain, as these rocks typically exhibit a bimodal hydraulic conductivity/porosity with fractures yielding water velocity of ~3 cm yr −1 , but comprising only 0.01% of the porosity, and a matrix porosity of ~1% yielding water velocity of ~0.003 cm yr −1 (Nordstrom et al, 1989).…”
Section: Introductionmentioning
confidence: 99%